A pulmonary mass with invasion into the heart. - Keane, Joseph; Mc Laughlin, Anne (My University, 2008)
We describe the case of a 58 year old woman who presented with bronchial atypical carcinoid found at surgery to invade the left atrium along the pulmonary veins. A right pneumonectomy and removal of a portion of the left atrium was performed. The patient made an excellent postoperative recovery. Three years later she presented in acute respiratory failure secondary to local recurrence. This is first case described in which recurrence after resection of bronchial carcinoid metastatic to the heart is described.
PUBLISHED
Keywords: Bronchial atypical carcinoid; Left atrium; Pulmonary veins; Acute respiratory failure